2006
DOI: 10.1162/jocn.2006.18.11.1843
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control is Slowed in Patients with Right Superior Medial Frontal Damage

Abstract: Inhibitory control is an essential part of behavior. Comprehensive knowledge of the neural underpinnings will shed light on complex behavior, its breakdown in neurological and psychological disorders, and current and future techniques for the pharmacological or structural remediation of disinhibition. This study investigated the neural mechanisms involved in rapid response inhibition. The stop signal task was used to estimate inhibitory speed in a group of neurologically normal control subjects and patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
185
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(197 citation statements)
references
References 30 publications
10
185
2
Order By: Relevance
“…Our results are consistent with previous studies demonstrating that the medial PFC is necessary for motor inhibition (4,9,16,17). In monkeys, microstimulation of the supplementary eye field within the medial prefrontal cortex improved performance on an oculomotor version of the SST by delaying saccade inhibition (9), and stimulation of the pre-SMA inhibited automatic unwanted actions while facilitating a desired alternative (10).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous studies demonstrating that the medial PFC is necessary for motor inhibition (4,9,16,17). In monkeys, microstimulation of the supplementary eye field within the medial prefrontal cortex improved performance on an oculomotor version of the SST by delaying saccade inhibition (9), and stimulation of the pre-SMA inhibited automatic unwanted actions while facilitating a desired alternative (10).…”
Section: Discussionsupporting
confidence: 92%
“…Previous work with this task provides evidence that both medial frontal regions, including the presupplementary motor area (pre-SMA), and more lateral regions, including the right inferior frontal gyrus (IFG; rIFG) and insula (Ins), are involved in stopping. However, the specific contributions of these regions to motor control are unresolved (2)(3)(4). Many functional imaging studies have demonstrated activation of right inferior frontal regions during stopping (2,(5)(6)(7)(8) and individual differences in response inhibition correlate with the magnitude of the IFG/Ins activation during the SST (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimentally induced microstimulation of preSMA neurons led to a greater proportion of switch trials being successful. Combined with the findings in humans that preSMA lesions affect stopping (Floden and Stuss, 2006;Nachev et al, 2007) and that the preSMA is directly connected with the IFC and the STN region , these findings strongly implicate the dorsomedial frontal cortex in control over motor responses. Future research will need to precisely determine how the nodes in this network interact.…”
Section: Neurophysiological Mechanisms Of Stoppingsupporting
confidence: 52%
“…Two recent studies identified a third critical node for the stopping process in the dorsomedial frontal cortex, including the presupplementary motor area (preSMA) (Floden and Stuss, 2006;Nachev et al, 2007). Interestingly, the preSMA was also found to be directly connected with both the right IFC and the right STN region via white matter tracts (Fig.…”
Section: Lesion and Imaging Studies In Humansmentioning
confidence: 99%